Teaching of Reading through PowToon: Practices and Students’ Attitude - Vonti, Lungguh Halira; Sutisna, Entis; Wahyuni, Asih (FKIP Universitas Lampung, 2020)
Technology has been in active use for a long time particularly in higher educational institutions. Mainly, technology provides various opportunities to enhance students’ performance to language learning. This present paper discusses the implementation and integration a technologyengagement teaching strategy with the aid of PowToon by focusing on students’ vocabulary mastery and their reading comprehension. This study presents the teaching practices that occur through such an activity by applying Powtoon as a multimodal learning tool to enhance students’ vocabulary mastery and reading comprehension. In addition, in the second section of this paper, this paper presents the students’ attitude toward the teaching of reading through Powtoon. This paper concludes with comments about both the extent of Powtoon as a multimodal learning tool and about the future of teaching reading comprehension through technology in a multimodal world. Keywords: technology, language learning, PowToon. DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202015